Maturity-onset Diabetes of the Young (MODY): How Much Can We Detect? - Gökhan UYGUN; Akif AYAZ; Mustafa KANAT (Bezmiâlem Science, 2025)
Objective: This study aims to assess the characteristics of patients who underwent genetic analysis with suspicion of maturity-onset diabetes of the young (MODY). Methods: Forty patients who met the criteria of measurable serum fasting C-peptide levels, positive family history, and autoantibody negativity and were diagnosed with diabetes at a young age were analyzed for demographic, clinical, laboratory and molecular test results. A comprehensive MODY panel examining a total of 21 genes [hepatocyte nuclear factor 4 alpha (HNF4A), glucokinase (GCK), HNF 1 alpha (HNF1A), pancreatic and duodenal homeobox 1, HNF 1 beta (HNF1B), neurogenic differentiation 1, kruppel-like factor 11, carboxyl ester lipase, paired box gene 4, insulin, B-lymphocyte kinase, adenosine triphosphate binding cassette sub-family C member 8, potassium inwardly rectifying channel subfamily J member 11, AKT2, GLI-similar 3, glutamate dehydrogenase 1, hydroxyacyl‑CoA dehydrogenase, insulin receptor, solute carrier family 2 member 2, wolfram syndrome 1, zinc finger protein 57] in 30 patients (75%) with next-generation sequencing method and variants detected in 10 patients (25%) using a short panel including GCK, HNF1A, HNF1B and HNF4A genes were analyzed using different databases (online mendelian inheritance in man, database of single nucleotide polymorphisms, genome aggregation database, human gene mutation database). Results: Overall, 11 variants in 7 different genes were detected in 10 patients (25%). Sixty per cent (n=6) of the mutation-positive patients were treated with insulin. Serum fasting C-peptide levels (1.18 vs 1.26 ng/mL, p=0.891) and age at diabetes diagnosis (26.5 vs 29.0 years, p=0.860) were not different between the mutation-positive and mutation-negative groups. Conclusion: Despite the improved diagnosis, MODY diagnosis is still missed and a significant number of patients are unnecessarily treated with insulin. In particular, individuals diagnosed with diabetes at a young age, with negative autoantibodies and measurable serum C-peptide levels, should be evaluated for MODY.